Dynamics of Interpersonal Relationships in Virtual Guidance and Counseling for BK Students: Challenges, Opportunities, and Intervention Strategies - Nurasyah, Nurasyah; Putri, Rini Fadhillah; Fitriani, Enny (PT Inovasi Pratama Internasional, 2025)
The counseling process has been significantly changed by advances in information and communication technology. The digital era has paved the way for virtual counseling services, which allow wider, more flexible, and anonymous access for those who need it, especially students. One of the important services provided to students to support their emotional, social, and academic growth is counseling. Counseling in higher education is increasingly being done virtually due to the rapid development of information technology. The purpose of this study is to investigate the dynamics of interpersonal relationships in virtual counseling, find problems, and find opportunities and intervention strategies that may be used in this situation. It is important to understand these challenges and create useful solutions for them. Some of the main problems that are often faced include difficulties in building strong emotional relationships, limitations in non-verbal interactions, and technical problems that can interfere with communication. The research method is a qualitative descriptive method by taking data from several libraries that are used as consideration. After reviewing the literature from various related research sources, this article concludes that although virtual counseling services present some technical problems and limitations in non-verbal interactions, they also offer greater opportunities. Appropriate intervention strategies include technology skills training, use of safe platforms, and approaches that rely more on effective communication skills.